Odia Encyclopaedia Orissana Part 3 - Mansingh, Mayadhar (Utkal University, 1964)
Odiya Encyclopaedia content to deliver the knowledge of odiya alphabets and various odiya words starting from first letter of Odiya alphabets. Whole book is targeted to deliver clear knowledge on various odiya words and its uses.
Keywords: Odia; Encyclopedia; Odia